2022
DOI: 10.3390/cancers14040894
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ABCC Genes by Cisplatin Depends on the CoREST Occurrence at Their Promoters in A549 and MDA-MB-231 Cell Lines

Abstract: Although cisplatin-based therapies are common among anticancer approaches, they are often associated with the development of cancer drug resistance. This phenomenon is, among others, caused by the overexpression of ATP-binding cassette, membrane-anchored transporters (ABC proteins), which utilize ATP to remove, e.g., chemotherapeutics from intracellular compartments. To test the possible molecular basis of increased expression of ABCC subfamily members in a cisplatin therapy mimicking model, we generated two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Previous evidence showed other mechanisms that regulated ABCC10 expression. Transcriptional activation of ABCC10 gene was Cisplatin-induced and histone acetylases EP300-dependent in the presence of p53 [ 40 ]. As one of the most common epigenetic RNA modifications, N 6 -methyladenosine (m 6 A) modification mediated the expression of ABCC10.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence showed other mechanisms that regulated ABCC10 expression. Transcriptional activation of ABCC10 gene was Cisplatin-induced and histone acetylases EP300-dependent in the presence of p53 [ 40 ]. As one of the most common epigenetic RNA modifications, N 6 -methyladenosine (m 6 A) modification mediated the expression of ABCC10.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-binding cassette transporter (ABC) proteins bound with membrane were involved in resistance to antitumor drugs by controlling drug efflux . Recently, two articles showed an association between LSD1 and ABC family members in drug resistance in BC. , LSD1 inhibition caused a decline in transcription of ABCC1 and ABCC10 induced by I-CBP112, so LSD1 was identified as a crucial repressor of ABC proteins . In addition, pharmacological inhibition of the CoREST enzymatic subunits (LSD1 and HDACs) recovered ABCC gene responsiveness to cisplatin …”
Section: Mechanisms Of Lsd1-related Drug Resistance Of Cancersmentioning
confidence: 99%
“…31 In addition, a research group clearly pointed out that responsiveness of ABCC gene to cisplatin was restored by restraining LSD1 and histone deacetylases (HDACs) (CoR-EST enzymatic subunits) in A549 cells. 63 Altogether, LSD1 not only plays a role in regulating cellular malignant biological properties but also functions at controlling the expression of genes related to drug efflux.…”
Section: Role Of Lsd1 Inmentioning
confidence: 99%
“…The same compounds gave downregulation of ERα, at both transcriptional and non-transcriptional levels, through modulation of miR-181a-5p expression ( Benedetti et al, 2019 ; Benedetti et al, 2021 ). The reduction of activity of LSD1, obtained by either pharmacological or genetic approach, could prevent resistance to antitumor agents in breast as well as other cancer models ( Lu et al, 2018 ; Sobczak et al, 2022 ). In blood cancers, various studies demonstrated the contribution of LSD1 to the onset and progression of AML ( Lokken and Zeleznik-Le, 2012 ).…”
Section: Introductionmentioning
confidence: 99%